Clinical Features and Outcomes of Dengue Fever in a Tertiary Paediatric Hospital in Dhaka, Bangladesh - Md Aktaruzzaman; Sharmin Afroze; Farhana Ahmed; Mostafizur Rahman; Gazi Abdul Bari; Kiriti Kumar Dhali (International Journal of Human and Health Sciences (IJHHS), 2026)
Globally, children, adolescents, and young adults constitute the largest burden of Dengue. Early diagnosis is crucial for timely intervention and better outcome. This cross-sectional study was conducted among 51 children with dengue fever admitted in the Department of Paediatrics, Dr. M R Khan Shishu Hospital & Institute, Dhaka, Bangladesh, between April and September of 2025, to assess the clinical features of the dengue infection in children and to evaluate the outcomes. The most common age of presentation was between 2 and 10 years. The most common presenting symptom was fever less than 5 days, seen in 51% cases followed by body ache (47%) and anorexia (38%) followed by rash (28%), diarrhea (22%) and cough and cold (22%). Vomiting (55%) and abdominal pain (37%) were common warning features followed by shock (18%). No co-morbidities were found. All the patients were recovered and discharged to home. Dengue in children bears the common presentation as evident by other research studies. Early suspicion and effective management can lead to a favorable outcome. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 236-239